Perancangan Motion Graphic Edukasi Kami Juga Manusia, Anxiety Disorder - Pratama, Indra Wahyu; Erlyana, Yana (Rekam, 2024)
Mental health, is a health issue that is no less important than physical health, but unfortunately public awareness of mental health issues is still very lacking. The lack of public awareness of mental health disorders is influenced by several factors, where one of the most influential factors is the low level of public knowledge about mental health, so that there is an error in the public's perspective on the survivors of mental health disorders themselves. This of course can lead to mistreatment of survivors of mental health disorders, potentially stigmatizing treatments. Based on these data, this study aims to use the right learning media to change the public's perspective on mental health disorders in order to reduce the existing stigmatization. The method used is the design thinking method which is a method of developing a product that begins with efforts to answer problems that exist in society. The results of this study a learning media in the form of video motion graphics with cartoon visual style and a way of delivering information with an emotional and rational approach has its own charm for the audience.